LEPTIN RECEPTOR GENE POLYMORPHISMS AND Its EFFECT ON SOME PRODUCTIVE AND PHYSIOLOGICAL TRAITS IN LOCAL IRAQI CHICKEN - Ratha, Mohammad A. K. Al Ani; Bassam G.M. Al Khatib, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was conducted in poultry farm in college of agricultural engineering Sciences - University of Baghdad - animal production department. In this study 100 laying hens of local Iraqi chickens were used with age 67day old, were placed in individual cages, each cage was numbered from 1 to 100, for the period from 26/10/2021 till 24/7/2022 to detect the different genotypes of LEPR gene, determining the frequency and percentage of the relevant genotypes local Iraqi chickens, , Productive traits were measured from the sexual maturity in to 100 days for each chicken, the blood samples were collected from 100 laying hens at the 38 weeks of age from the brachial vein, the PCR reaction will done using specific primers, Then sanger sequencing technique were done and three genotypes of leptin receptor gene were obtained TT genotype (wild) , TC (heterozygous) and CC genotype( mutant), the C allele frequency were 0.74 had high significant difference (p